A compact 3D-printed interface for coupling open digital microchips with Venturi easy ambient sonic-spray ionization mass spectrometry1. Issue 5 (7th March 2015) - Hu, Jie-Bi; Chen, Ting-Ru; Chang, Chia-Hsien; Cheng, Ji-Yen; Chen, Yu-Chie; Urban, Pawel L.
<x xml:space="preserve">Abstract</x> We demonstrate a simple user-friendly interface for integrating digital microfluidics with mass spectrometric detection.